B lymphocytes as antigenpresenting cells in autoimmune pathologies - Kuklina, E.M.; Smirnova, E.N.; Baidina, T.V.; Nekrasova, I.V.; Balashova, T.S.; Sursyakova, N.V.; Danchenko, I.Yu. (Perm Federal Research Centre Journal, 2017)
B cell expression of the molecules involved in antigen presentation for T cells, CD80/CD86 and HLA-DR, as well as a T lymphocyte response to exo-/auto-antigens presented by autologous B lymphocytes in mixed culture have been studied in patients with organo-specific autoimmune diseases. The increased ex vivo expression of costimulating molecule CD80 by memory B cells (CD19+CD27+) of autoimmune thyreoidite (AIT) patients was shown, as well as the in vitro amplification of the expression of CD80 (for multiple sclerosis (MS) and AIT patients) and HLA-DR (for AIT patients) in B cell polyclonal activation, which is evidence of the increasing B cell potential antigenpresenting activity in autoimmune diseases.This proposal is confirmed by a higher proliferative response of AIT patient CD4+Т lymphocytes to the exoantigen tetanus toxoid presented by autologous B lymphocytes. Besides, in AIT patients, the CD4+Т cell proliferative response to the key autoantigen, associated with the pathology, thyroid peroxidase, was higher than that of the healthy donors, though for the second autoantigen, thyroglobulin, the same effect was not revealed.Analogous investigations toward autoimmune diabetes mellitus patients have revealed the ability of B lymphocytes, preincubated with autoantigens, to induce the CD4+Т cell proliferative response, however, out of three autoantigens studied, the increased proliferation index was detected only for proinsulin, but not for insulin or glutamic acid decarboxylase. Considering the intensive B cell infiltration of autoimmune attack target tissues, which is characteristic of all the diseases investigated, the antigen presenting activity of B lymphocytes may serve as one of the mechanisms of autoimmune processes induction or progression.